Analisis Struktur Komparatif Industri Pada Perkembangan Industri - Firda Ananda Yulia Sari; Alvazaki Ikbar Maulana; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the comparative structure of industry and its development in various economic sectors. This study uses a quantitative approach by analyzing secondary data obtained from various reliable sources, including industry reports, government publications, and economic databases. The analytical methods used include financial ratio analysis, regression analysis, and cluster analysis to identify patterns and trends in industry structure. The research results show that there are significant differences in industrial structure between different sectors, with some sectors showing faster growth and better adaptation to technological and market changes. These findings provide important insights for policy makers and industry players to formulate more effective strategies in managing industrial development and increasing economic competitiveness.